The Contemporary Dowry Problematic: Exploring the Role of the Study of Religion in Bridging the Gap between Theory and Practice - Bradley, Tamsin; Tomalin, Emma (Religions of South Asia, 2010)
This article explores the contemporary dowry problematic through a study of religions perspective. The argument made is that for religious women challenges to dowry will often be made by them from within their religious tradition. Whilst feminist scholars of religion recognize the role that it plays in shaping patriarchal practices such as dowry, ignoring the significance of religion in the lives of many women will only serve to marginalize them further from the anti-dowry campaign. This article considers what anti-dowry activists, who are mainly secular, can gain from a more sympathetic view of religion.